Processamento discursivo e executivo pós-traumatismo cranioencefálico - Pereira, Natalie (2015)
This dissertation contains two empirical articles which investigated the communication skills and executive functions of adults with traumatic brain injury (TBI) upon hospital admission (inpatients) and after hospital discharge (outpatients). The aim of the first study was to compare discursive, pragmatic, lexical-semantic, reading and writing skills between inpatients with TBI (iTBI) and adults with no neurological damage. Our results showed between-group differences on all parameters evaluated, with control participants outperforming the iTBI group across all measures used in the study. The aim of the second investigation was to identify differences between outpatients with mild or severe TBI (oTBI) and healthy adults on communicative and executive functions, as well as to investigate associations and dissociations between patterns of impairment in the oTBI sample. The two groups differed in their performance on conversational and narrative discourse tasks, as well as on the following executive functions: planning, cognitive flexibility, working memory, processing speed and inhibitory control. Overall, the findings suggested that even subjects with relatively mild lesions and a theoretically good prognosis may experience impairments in discourse processing. The patient group was then further divided according to TBI severity, and differences in executive functions were identified between these two subgroups, as well as between each of these categories and the control group. Patients with severe TBI performed worse than control participants and subjects with mild TBI, and differences between patients with mild and severe TBI were identified in both studies. Lastly, the TBI groups showed dissociations between impairments in rule maintenance and processing speed, and associations between cognitive performance on planning tasks. These findings contributed to the current literature on the continuum of communicative and executive impairment profiles across all levels of TBI severity. The analyses performed in this dissertation may be used in public health services to perform a more accurate assessment of patients with TBI and improve prognostic accuracy, since some impairments may have an impact on global functioning and affect the length of the post-TBI recovery period.